El Nino-like pattern in Ice Age Tropical Pacific Sea surace temperature - Koutavas, Athanasios; Lynch-Stieglitz, Jean; Marchitto, Thomas M.; Sachs, Julian P. (Science, 2002)
Sea surface temperatures (SSTs) in the cold tongue of the eastern equatorial Pacific exert powerful controls on global atmospheric circulation patterns. We examined climate variability in this region from the Last Glacial Maximum (LGM) to the present, using a SST record reconstructed from magnesium/calcium ratios in foraminifera from sea-floor sediments near the Galápagos Islands. Cold-tongue SST varied coherently with precession-induced changes in seasonality during the past 30,000 years. Observed LGM cooling of just 1.2°C implies a relaxation of tropical temperature gradients, weakened Hadley and Walker circulation, southward shift of the Intertropical Convergence Zone, and a persistent El Niño–like pattern in the tropical Pacific. This is contrasted with mid-Holocene cooling suggestive of a La Niña–like pattern with enhanced SST gradients and strengthened trade winds. Our results support a potent role for altered tropical Pacific SST gradients in global climate variations.
id: 644